Aqueous Humor Ferritin in Hereditary Hyperferritinemia Cataract Syndrome. Issue 4 (April 2015) - Lenzhofer, Markus; Schroedl, Falk; Trost, Andrea; Kaser-Eichberger, Alexandra; Wiedemann, Helmut; Strohmaier, Clemens; Hohensinn, Melchior; Strasser, Michael; Muckenthaler, Martina U.; Grabner, Guenther; Aigner, Elmar; Reitsamer, Herbert A.
ABSTRACT: Purpose: Hereditary hyperferritinemia cataract syndrome (HHCS) is a rare autosomal dominant hereditary disease, characterized by hyperferritinemia but with absence of body iron excess and early onset of bilateral cataracts. Although 5- to 20-fold increased serum ferritin concentrations have been reported in HHCS patients, data of ferritin levels in aqueous humor have not been obtained. We therefore aimed to investigate the ferritin levels in aqueous humor and serum and further present histological and ultrastructural data of the lens. Methods: During cataract extraction and intraocular lens implantation, aqueous humor and lens aspirate of a 37-year-old HHCS patient were obtained from both eyes. Ferritin levels in serum and aqueous humor were quantitatively analyzed via immunoassays in the HHCS patient and healthy control subjects (n = 6). Lens aspirate in HHCS was analyzed histologically and at the ultrastructural level. Further, genetic mutation screening by polymerase chain reaction and DNA sequencing in blood was performed. Results: Serum ferritin levels in the control group were 142.2 ± 38.7 μg/L, whereas in the HHCS patient, this parameter was excessively increased (1086 μg/L). Analysis of ferritin in aqueous humor revealed 6.4 ± 3.8 μg/L in normal control subjects and 146.3 μg/L (OD) and 160.4 μg/L (OS) in the HHCS patient. DNA analysis detected a C>A mutation on position +18, a T>G mutation on position +22, a T>C mutation on position +24, and a T>G polymorphism on position +26 in the iron-responsive element of the light-chain ferritin (L-ferritin) gene. Conclusions: In the HHCS patient, a 23-fold (OD) to 25-fold (OS) increased aqueous humor ferritin level was detected. Therefore, the formation of bilateral cataract in HHCS is most likely a result of elevated aqueous humor ferritin. In addition, a novel mutation in this rare disease in the iron-responsive element of L-ferritin gene is reported. Abstract : Supplemental digital content is available in the text.